The Urgency of Islamic Religious Education Management in Strengthening the Value of Religious Moderation in the Digital Era - Muhammad Ilham Hidayat; M. Syahrul (Ikatan Cendikiawan Ilmu Pendidikan Islam (ICIPI), 2025)
The development of digital technology has brought significant changes in the educational landscape and religious practices, including in Islamic Religious Education (PAI). On the one hand, digitalization opens up opportunities to strengthen innovative and inclusive PAI learning, but on the other hand, it presents serious challenges in the form of the rapid flow of unverified religious information, the emergence of exclusive religious narratives, and the potential for the spread of intolerant and radical ideas in the digital space. This condition demands the strengthening of the value of religious moderation as a just, balanced, and tolerant principle of religion. This study aims to analyze the urgency of Islamic Religious Education management in strengthening the value of religious moderation in the digital era. This research uses a qualitative approach with the type of library research, through a critical study of the Qur'an, Hadith, policies of the Ministry of Religion, as well as scientific literature related to Islamic education management, religious moderation, and digitization of learning. Data analysis was carried out with a thematic, descriptive-contextual, and content analysis approach. The results of the study show that the main challenges of PAI in the digital era are not only technological, but also ideological and managerial. Strengthening PAI management, which includes planning, organizing, implementing, and supervising learning, has proven to have a strategic role in integrating the value of religious moderation systematically and sustainably. Effective PAI management allows Islamic education to function as an ideological bulwark against digital intolerance and radicalism, as well as a means of forming a moderate, inclusive, and social-peace-oriented religious character.